2018
DOI: 10.1002/jlb.5ri1017-401rr
|View full text |Cite
|
Sign up to set email alerts
|

Obesity as an immune-modifying factor in cancer immunotherapy

Abstract: Immunotherapy has achieved breakthrough status in many advanced stage malignancies and is rapidly becoming the fourth arm of cancer treatment. Although cancer immunotherapy has generated significant excitement because of the potential for complete and sometimes durable responses, there is also the potential for severe and occasionally life-threatening toxicities, including cytokine release syndrome and severe autoimmunity. A large body of work also points to a "metainflammatory" state in obesity associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 129 publications
(220 reference statements)
3
26
0
Order By: Relevance
“…236 Of special consideration is cytokine release syndrome or "cytokine storm" and immunotherapy-induced immune-related adverse events (irAEs) that may be potentially exacerbated in obesity, reported in one mouse obesity study in tumor-free mice. 229,247 In our hands, however, immunotherapy does not induce cytokine release syndrome in obese mice with tumors (unpublished observations).…”
Section: Ob E S It Y the MI Crob I Ome And The Ob E S It Y Par Asupporting
confidence: 50%
See 3 more Smart Citations
“…236 Of special consideration is cytokine release syndrome or "cytokine storm" and immunotherapy-induced immune-related adverse events (irAEs) that may be potentially exacerbated in obesity, reported in one mouse obesity study in tumor-free mice. 229,247 In our hands, however, immunotherapy does not induce cytokine release syndrome in obese mice with tumors (unpublished observations).…”
Section: Ob E S It Y the MI Crob I Ome And The Ob E S It Y Par Asupporting
confidence: 50%
“…While those studies find an obesity‐ICB efficacy link regardless of sex for most survival measures, one study found the obesity‐associated boost in ICB efficacy for males only 236 . Of special consideration is cytokine release syndrome or “cytokine storm” and immunotherapy‐induced immune‐related adverse events (irAEs) that may be potentially exacerbated in obesity, reported in one mouse obesity study in tumor‐free mice 229,247 . In our hands, however, immunotherapy does not induce cytokine release syndrome in obese mice with tumors (unpublished observations).…”
Section: Obesity the Microbiome And The Obesity Paradox In Immune Cmentioning
confidence: 66%
See 2 more Smart Citations
“…Consistent with our finding in HKBC, a recent study reported a significant association between higher expression of CD8+ T-cell signatures and increasing BMI in 1,154 breast cancer patients from the Nurses' Health Study 28 . The link between obesity and breast cancer involves multiple mechanisms that may interplay with each other such as chronic inflammation, estrogen production, growth factor stimulation, and altered metabolism 29 . Future large studies are warranted to follow up this observation.…”
Section: Discussionmentioning
confidence: 99%